A Systematic Review of Drug-Loaded Electrospun Nanofiber-Based Ophthalmic Inserts - Safaa Omer; Romána Zelkó (MDPI AG, 2021)
Currently, ocular inserts and nanoparticles have received much attention due to the limited bioavailability of conventional eye preparations and the toxicity problems of systemic drug administration. The current systematic review aims to present recent studies on the use of electrospun nanofiber-based ocular inserts to improve the bioavailability of drugs used for different ophthalmic diseases. A systematic search was performed in PubMed, Ovid Medline, Web of Science, ScienceDirect, Scopus, Reaxys, Google Scholar, and Google Patents/Espacenet taking "drug-loaded", "nanofibers", and "ophthalmic inserts" and their equivalent terms as keywords. The search was limited to original and peer-reviewed studies published in 2011-2021 in English language. Only 13 out of 795 articles and 15 out of 197 patents were included. All results revealed the success of nanofiber-based ocular inserts in targeting and improved bioavailability. Ocular inserts based on nanofibers can be used as safe, efficient carriers for the treatment of anterior and posterior eye diseases.